Evaluasi Strategi Perencanaan Pajak Pertambahan Nilai Atas Pencabutan Peraturan Perpajakan Terhadap Laba Perusahaan - Syafrizal, Alvi; Saraswati, Erwin (Telaah Ilmiah Akuntansi dan Perpajakan, 2023)
This research aims to analyze and empirically prove the effect of tax expense, intangible assets, and foreign ownership on indications of transfer pricing practices with firm size as the moderating variable. This research employs the causal quantitative method. The samples of 24 manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020 were selected through purposive sampling with specified criteria, and analyzed by Multiple Linear Regression and Moderated Regression Analysis (MRA). The results indicated that tax expense and intangible assets had a negative effect on indications of transfer pricing practices, but foreign ownership had no effect. Firm size was proven to strengthen the effect of tax expense on indications of transfer pricing practices, but firm size did not moderate the effect of intangible assets and foreign ownership on indications of transfer pricing practices.